PENGEMBANGAN METODE PEMBELAJARAN SITUASIONAL INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN BAHASA ORAL ANAK TUNARUNGU - Suparno . (Jurnal Cakrawala Pendidikan, 2004)
A studying the fonn of action research has been conducted to determine the possibility ofemploying a situational interactive approach in the teaching-learning process of deaf children to increase their oral language skill. The study also aimed to explore the teaching-learning procedure to use to improve their oral language skill. With students of a state special school for the deaf in Yogyakarta as the population, the study was conducted in an oral language skill class ofthirty-two deafchildren in two cycles consisting offourc1ass sessions through the steps ofreconnaissance, planning, implementation combined with observation, and re flection. Modifications of the teaching-learning process were conducted as treatment by the classroom teachers in collaboration with the researcher. The data were collected by administering achievement tests and analyzed with qualitative and quantitative methods. The results indicate that (1) the actions implemented improved the students' oral language skill, (2) the model of situational interactive approach used was more effective in increasing their orallaIiguage skill than the regular one, and (3) it is feasible to use this model to teach deafchildren. Key words: deafchildren, interactive situational approach.